A SUGGESTION FOR THE MEASUREMENT OF SOLVENCY. - Mackler, I. M. (The Accounting Review, 1942)
Abstract For many years accountants and credit men have used the current ratio as an index of the debt-paying ability of business enterprises. But the current ratio portrays only static conditions and it has been found necessary to use additional ratios in order to measure the dynamic aspects of business not shown by the balance sheet alone. The most common definition of the current ratio is that it is an expression of relationship between current assets and current liabilities. The criterion establishing the difference between a current asset and a fixed asset and a current liability and a fixed liability is respectively realization and liquidation within a period of one year from the date of the balance sheet. However, the maturities of current assets and current liabilities range through the year and no basis exists for the belief that the range of asset maturities averages out against the range of liability maturities with a resultant offsetting effect. A reliable measure of solvency should reveal the amount of funds that will be available to meet obligations as they fall due. To do this, all of the assets must be converted to cash value and expressed in relation to the liabilities as they mature.